The customization of Rural Extension and its implications for teaching - Vivien Diesel; Marcelo Miná Dias; Pedro Selvino Neumann (Universidade Federal do Norte do Tocantins, 2022)
This study examined the reconfigurations in the field of extension work and its potential influences in the academic discipline of rural extension. It recognizes that one of the ongoing changes has an institutional nature and is related to the adoption of a pluralist model of rural extension. It is argued that the adoption of a pluralist model leads to the recognition of a greater diversity of types of organizations active in the rural extension system, which favors the occurrence of processes of customization of normative references that are used to guide the extension field work. A comprehensive literature review was performed to characterize these dynamics in the global and Brazilian scope, exploring their implications for the rural extension teaching. The results suggest that this movement implies a scenario of professional profile disputes that reflects, ultimately, disputes over projects for rural development, which must be made explicit within the scope of teaching, highlighting their relationships with the normative references for action professional.